Solution‐Processed and Transparent Graphene Oxide/TiOx Gas Barrier via an Interfacial Photocatalytic Reduction. Issue 8 (5th March 2020) - Byeon, Jinhwan; Lee, Jong‐Hoon; Kim, Geunjin; Back, Hyungcheol; Park, Byoungwook; Kim, Jehan; Lee, Kwanghee
Abstract: A cost‐effective, flexible, and transparent gas barrier has been a main pursuit of research into plastics electronics. However, it is difficult to realize a high‐performance gas barrier on a plastic substrate via a solution process at low temperature. Here, by introducing an interfacial photocatalytic reduction between TiO x and graphene oxide (GO) films, a solution‐processed and transparent gas barrier film is demonstrated using reduced GO (rGO)/TiO x . A dramatic photochemical reduction of GO occurs at the interface between TiO x and the GO film under ultraviolet irradiation, which allows the fabrication of dense and uniform gas barrier films via a solution process at temperatures below 100 °C. In addition, the closely packed structure in the rGO film results in a decreased water vapor transmission rate (WVTR) of 0.37 g m −2 day −1 even with a thin rGO (<13 nm)/TiO x (7 nm) film, leading to a high transmittance of over 80% in the visible range. Abstract : A solution processed transparent gas barrier is developed via an interfacial photo‐catalytic reduction process, enabling the formation of uniform and closely packed film of reduced graphene oxide on the surface of titanium oxide. This finding provides detailed insight into fabricating solution‐processable gas barrier with high performance for plastic electronics.